childhood, image and teacher education: between experiences, knowledge and powers in early childhood education - Leite, Cesar Donizetti [UNESP]; Oliveira Camargo, Andreia Regina de (State Univ Rio De Janeiro, 2018)
The reflections around teacher training and the means by which it is treated in the educational contexts have major importance, due to the urgency of the topic as well as the multiplicity of ways to be dealt along with the teachers. From researches of images production, developed with children and teachers in the ambit of early childhood education, this text will reflect on the formative processes of teachers in the childhood education. In this context, there are a few relevant questions: what can the image do in the formative processes? In which ways may the teacher training help us to think about the childhood and the educational practices with little children? By which means may the childhood help us to think the work of teacher training. In this way, using the produced images, this text aims to operate in the circulation movement of the thought itself, in which the thought can, in its exteriority, experiment with words (language), childhood, image and teacher training, enabling ruptures to think about the child, the educators, the school, the knowledge, the doing, the powers, the action protocols, what to do with the children and how to deal with them, composing possibilities that overflow what is determined and legalized. As theoretical basis, we take authors such as G. Agamben, G. Deleuze e Michel Foucault.
Keywords: imagetic experiences; childhood; teacher training; early childhood education